Mechanism of the t-BuOM (M = K, Na, Li)/DMEDA-Mediated Direct C–H Arylation of Benzene: A Computational Study - Patil, Mahendra (Synthesis, 2020)
Over the past ten years, a combination of organic additive and t-BuOK/t-BuONa has been successfully used for the direct C–H arylation of arenes. Conceptually different from transition-metal-catalyzed cross-coupling reactions, these t-BuOK-mediated reactions have raised significant curiosity among organic chemists. Herein, a systematic computational study of each elementary step of the t-BuOM (M = K, Na, Li)/N1,N2-dimethylethane-1,2-diamine (DMEDA) mediated direct C–H arylation of benzene is detailed. The presented mechanistic proposal relies on the complexation and reaction of t-BuOM with DMEDA (additive), which leads to the formation of different complexes such as SED(M+)…PhI. These complexes mainly involve coordination of the metal ion (from t-BuOM) to the additive and iodobenzene via stabilizing cation–lone pair and cation–π interactions. Such complexation of a metal ion to an additive and iodobenzene not only ensures facile electron transfer to iodobenzene but also provides a lowest energy pathway for the subsequent radical addition and deprotonation step.
Keywords: C–H arylation; mechanism; DFT; cross-coupling; potassium tert-butoxide